Successful treatment with laparoscopy-assisted surgery for ileal perforation due to an ingested foreign body: A report of two cases. (2019) - Ito, Soichi; Tsuchitani, Yuma; Hashimoto, Souhei; Uemura, Takuji; Katsura, Kazunori; Abe, Takayuki; Sato, Koichiro; Kato, Hirotaka
Highlights: Small bowel perforation by an ingested foreign body (FB) is a rare abdominal emergency. Computed tomography scan is most effective but imperfect for diagnosis. Inquiring about FB ingestion and a high index of suspicion are very important. Laparoscopic surgery is effective even in this rare abdominal emergency. Extracorporeal handling of the affected small bowel is useful in this condition. Abstract: Introduction: Presently, the advantage of laparoscopic surgery is widely recognized and it is gaining popularity not only in elective abdominal surgeries but also in various kinds of emergent abdominal surgeries. This report describes two patients diagnosed with ileal perforation due to an ingested foreign body (FB)—a rare abdominal emergency—who were treated laparoscopically. Presentation of case: Both patients were brought in by an ambulance to our hospital, with complaints of increasing lower abdominal pain. Computed tomography scan revealed a small bowel perforation due to an ingested FB in both patients, and laparoscopy-assisted partial ileal resection was immediately performed. Their postoperative recoveries were uneventful. Discussion: Both patients with this rare abdominal emergency were successfully treated with laparoscopic surgery. Its feasible diagnostic and therapeutic abilities and decreased invasiveness contributed to their uneventful and fast recoveries. Extracorporeal handling of the affected small bowel via mini-laparotomy was useful in this setting as it was safe, fast, and cost-effective. Conclusion: Laparoscopic surgery is effective, even for this rare abdominal emergency. Moreover, laparoscopy-assisted surgery accompanying mini-laparotomy is a rational treatment approach, especially for this condition.